The Effect of Sanctions on Cooperative Behavior: A Study on Medium Trust Individuals in the Context of Corruption - Dewi Rosiana; Achmad Djunaidi; Indun Lestari Setyono; Wilis Srisayekti (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
This study aims to describe the effect of sanctions (individual sanctions, collective sanctions, and absence of sanctions) on cooperative behavior of individuals with medium trust in the context of corruption. Both collective sanctions and individual sanctions, are systemic, which means sanctioning behavior is exercised not by each individual but by the system. Cooperative behavior in this context means choosing to obey rules, to reject acts of corruption and to prioritize public interests rather than the personal interests. Conversely, corruption is an uncooperative behavior to the rules, and ignores the public interest and prioritizes personal interests. Research subjects were 62 students. The Chi-Square Analysis was used to see the association between the variables and the logistic regression model was applied to describe the structure of this association. Individual sanction is recommended as punishment to medium trust individuals to promote cooperative behavior in the context of corruption. The results showed that individuals with medium trust had more cooperative behavior.